Alterations in the immune system persist after one year of convalescence in severe COVID-19 patients - Abarca-Zabalía, Judith; González-Jiménez, Adela; Calle-Rubio, Myriam; López-Pastor, Andrea R.; Fariña, Tomás; Ramos-Acosta, Carlos; Anguita, Eduardo; Urcelay, Elena; Espino-Paisán, Laura (Frontiers in Immunology, 2023)
Introduction: Severe COVID-19 originates a myriad of alterations in the immune system during active disease, especially in the T and NK cell compartments, but several studies in the last year have unveiled some alterations that persist in convalescence. Although most of the studies follow the participants for a short recovery time, studies following patients up to three or six months still find alterations. We aimed at evaluating changes in the NK, T and B cell compartments after severe COVID-19 in participants with a median recovery time of eleven months. Methods: Eighteen convalescent of severe COVID-19 (CSC), 14 convalescent of mild COVID-19 (CMC) and nine controls were recruited. NKG2A, NKG2C, NKG2D and the activating receptor NKp44 were evaluated in NKbright, NKdim and NKT subpopulations. In addition, CD3 and CD19 were measured and a basic biochemistry with IL-6 levels was obtained. Results: CSC participants showed lower NKbright/ NKdim ratio, higher NKp44 expression in NKbright subpopulations, higher levels of serum IL-6, lower levels of NKG2A+ T lymphocytes and a trend to a lower expression of CD19 in B lymphocytes compared to controls. CMC participants showed no significant alterations in the immune system compared to controls. Conclusions: These results are concordant with previous studies, which find alterations in CSC weeks or months after resolution of the symptoms, and point to the possibility of these alterations lasting one year or more after COVID-19 resolution.